2012
DOI: 10.1097/prs.0b013e318262f06e
|View full text |Cite
|
Sign up to set email alerts
|

Human Acellular Dermis versus No Acellular Dermis in Tissue Expansion Breast Reconstruction

Abstract: The presence of acellular dermis did not increase the incidence of tissue expander loss, despite a doubling of frequency of seroma. Prior radiation and use of acellular dermis did culminate in a prohibitively high loss rate of the tissue expander.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 0 publications
3
65
1
3
Order By: Relevance
“…No significant differences in seroma formation were found among the ADM groups (P = 0.741) ( Table 3). In addition to axillary dissection, which was found to be a significant variable (P = 0.001) in the univariate analysis, the existing literature suggests that factors such as age, BMI, DM, the amount of ADM, and implant size are closely related to seroma formation [1,[8][9][10][11]. Our results remained significant after adjusting for these factors.…”
Section: Amount Of Drained Serum and Drain Maintenance Periodsupporting
confidence: 55%
See 2 more Smart Citations
“…No significant differences in seroma formation were found among the ADM groups (P = 0.741) ( Table 3). In addition to axillary dissection, which was found to be a significant variable (P = 0.001) in the univariate analysis, the existing literature suggests that factors such as age, BMI, DM, the amount of ADM, and implant size are closely related to seroma formation [1,[8][9][10][11]. Our results remained significant after adjusting for these factors.…”
Section: Amount Of Drained Serum and Drain Maintenance Periodsupporting
confidence: 55%
“…Chun et al [1] reported that the use of ADM increased the risk of seroma occurrence by 4.24 times, and of infection by 5.37 times, whereas Parks et al [11] reported that it increased the risk of seroma by almost 2 times. Furthermore, Jordan et al [7] reported that such an increase in the occurrence of seroma multiplied the chance of tissue expander removal by 4.42 times and of infection-induced tissue expander removal by 6.71 times [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have also shown increased rates of seroma formation in patients who have undergone AlloDerm-associated (LifeCell Corp., Branchburg, NJ) reconstructions [16,17,22,23], with an incidence ranging from 0 to 9 % in one particular systematic review [1]. Poor contact between the ADM and overlying tissues secondary to irregularity at the soft tissue interface and intentional under inflation of the tissue expander have been cited as reasons for these increased seroma rates [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…In the original report of Breuing as well as in five subsequent randomized studies the effectiveness and success of immediate reconstruction when using ADM were proven [38,41,42,[47][48][49]. In these retrospective studies, the overall incidence of complications was between 6,9% and 25%.…”
mentioning
confidence: 95%